Influence of thermal hydrolysis-anaerobic digestion treatment of wastewater solids on concentrations of triclosan, triclocarban, and their transformation products in biosolids. (March 2017) - Armstrong, Dana L.; Rice, Clifford P.; Ramirez, Mark; Torrents, Alba
Abstract: The growing concern worldwide regarding the presence of emerging contaminants in biosolids calls for a better understanding of how different treatment technologies at water resource recovery facilities (WRRFs) can influence concentrations prior to biosolids land application. This study focuses on the influence of solids treatment via the Cambi Thermal Hydrolysis Process™ in conjunction with anaerobic digestion (TH-AD) on concentrations of triclosan (TCS), triclocarban (TCC), and their transformation products in biosolids and sludges. Concentrations of the target analytes in biosolids from the TH-AD process (Class A), sludges from the individual TH-AD treatment steps, and limed biosolids (Class B) from the same WRRF were compared. TCC concentrations were significantly lower in Class A biosolids than those in the Class B product - a removal that occurred during thermal hydrolysis. Concentrations of TCS, methyl triclosan, and 2, 4-dichlorophenol, conversely, increased during anaerobic digestion, leading to significantly higher concentrations of these compounds in Class A biosolids when compared to Class B biosolids. Implementation of the TH-AD process had mixed effect on contaminant concentrations. Highlights: Significant reduction of TCC concentrations occurred during thermal hydrolysis. TCS, MeTCS, and 2, 4-DCP were concentrated due to anaerobic digestion. TCS, MeTCS, and 2, 4-DCP were not impacted by thermal hydrolysis.